Obsessions Across Two Cultures: A Comparison of Belgian and Turkish Non-clinical Samples - Ozcanli, Fulya; Ceulemans, Eva; Hermans, Dirk; Claes, Laurence; Mesquita, Batja (Frontiers in Psychology, 2019)
There is a growing interest in the role of culture in Obsessive Compulsive Disorder, yet cultural studies to date have suffered from methodological limitations and lack a clear theoretical framework. In the current study, we adopted a rigorous methodological approach, and a clear cultural psychological framework. We compared the structure and frequency of obsessions in non-clinical samples (N=706) from Belgium, a Western culture, and Turkey, a non-Western cultural context. Obsessions were measured by a newly compiled instrument that included a broad range of obsessions. Cross-cultural equivalence of the structure of obsessions was assessed both in the pooled data, and in each culture separately. At an abstract level, we found a two-factor structure that was cross-culturally invariant, and that fit both cultures equally well. These two types of obsessions each corresponded with a different model of agency. Compared to the Turkish sample, the Belgian sample reported more obsessions that can be understood from a disjoint (independent) model of agency as frequently found in Western cultures, whereas the Turkish sample, compared to their Belgian counterparts, reported more obsessions that can be tied to a conjoint (shared) model of agency as frequently found in non-Western cultural contexts. Differences in the prevalent types of obsessions were systematic and interpretable, therefore. In addition to the cross-culturally equivalent two-factor structure, we found culture-specific factor solutions; these solutions point to cultural differences in the experience of obsessions that have yet to be fully understood. In the Discussion, we outline future directions of the research on culture and obsessions.